Ancylostoma Induced Acute Haemorrhagic Gastroenteritis in a Male Adult Kanni Dog: An Uncommon Incidence - Subramanian,; Ganapathy, Selvaraju (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Ancylostoma caninum is the major cause of canine hookworm disease in most tropical and subtropical  regions of the world and anaemia is the main pathological  effect caused by blood sucking activity of the worms  (Umeakuana et al., 2020). The disease is more often seen  in young puppies or dogs under one year of age, by  transmammary route of infection and adult dogs are  mostly asymptomatic owing to their acquired immunity.  Nevertheless, the dog may show iron deficiency and develop  a microcytic hypochromic anaemia. Severe anaemia is  commonly encountered in puppies and could be successfully  treated by appropriate therapy, which includes blood  transfusion (Jasmin et al. 2020). Hence, severe anaemia  requires fecal examination and presence of many eggs in  feces is suggestive of acute ancylostomosis, though clinical  signs could be observed during the prepatent phase itself  (Lefkaditis, 2001). This document reports an unusual case of  ancylostoma induced acute haemorrhagic gastroenteritis  and its management in an adult male Kanni dog.
Keywords: Ancylostoma; caninum; canine; hookworm; disease